Factors Associated with Shoulder Pain in Office Workers - Risva Aprina Fitri Lestari; Yona Wia Sartika Sari; Muhammad Hasan Azhari (Indonesian Health Issue, 2026)
Background:Shoulder pain is a common musculoskeletal complaint among office workers due to monotonous work activities, static postures, and long work hours. Factors such as age, tenure, daily work hours, and work posture are thought to contribute to shoulder pain.Objective:This study aims to analyze the relationship between age, length of service, length of work, and work posture with the incidence of shoulder pain in office workers.Method:This research is a quantitative analytical study with a cross-sectional design. The sample consisted of 40 office workers at Kesdam II Sriwijaya who experienced shoulder pain, selected using a total sampling technique. Data collection was conducted using a structured questionnaire to obtain data on age, length of service, daily work hours, shoulder pain complaints, and work posture assessment based on respondents' self-reports. Data analysis was performed bivariately using the chi-square test to determine the relationship between variables..Results:As many as 75% of respondents reported complaints of shoulder pain.The results of the bivariate analysis showed a significant relationship between age (p = 0.023), length of service (p = 0.012), and length of service (p = 0.041) with shoulder pain. However, no significant relationship was found between work posture and shoulder pain (p > 0.05), either individually or after combining the p-values (p = 0.507).Conclusion:There was a significant association between age, length of service, and length of work with the incidence of shoulder pain in office workers, while work posture did not show a statistically significant association. Preventive measures through ergonomic interventions, work duration management, and increased awareness of work posture are still needed to reduce the risk of shoulder pain in office workers.